Roles of Fructooligosaccharides and Phytase in Broiler Chickens: Review - Shang, Yue; Kim , Woo Kyun (International Journal of Poultry Science, 2016)
Supplementing prebiotics and enzymes into poultry diets are among the most effective strategies in order to improve nutrient utilization, growth performance, intestinal development, immune system, intestinal microbiome and gut health. Fructooligosaccharides (FOS) is one of the most common prebiotics used in poultry. It has been reported that dietary FOS supplementation in broilers improved body weight gain, feed conversion and carcass yield. It could also enhance intestinal development, improve immune responses and increase short chain fatty acid fermentation of the broilers. Furthermore, Salmonella infection has been reduced by FOS supplementation into broiler diets. Phytase supplementation is one of the successful enzyme application in poultry. Phytase supplementation has increased body weight gain, Ca and P utilization and bone development in broilers. The combination of prebiotics and phytase, based on the modes of action of each component has shown potential benefit in poultry. Prebiotics is capable of increasing gut fermentation, producing short chain fatty acid and reducing gut pH. It has been hypothesized that prebiotics supplementation could create an acidic environment, which is favorable for phytase, increasing phytase activity and P utilization in the intestine. Therefore, the combination of prebiotics and enzyme could be a potential strategy to improve gut health and nutrient utilization in poultry.